Cassava processing technology toolkit catalogue - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2022)
The purpose of this technology catalogue is to advance high quality cassava flour (HQCF) as a substitute for wheat in Africa. While Africa has the potential to increase its wheat production, it appears to be small in proportion to the massive demand for imported wheat. For example, Africa imported US $11 billion from eight European and North American countries in 2020, a massive expenditure of foreign reserves that could be better directed toward longer-term development goals. At the same time, cassava is well suited to African agricultural conditions and may be processed into flour that can be substituted for wheat as documented in this catalogue. In the past, cassava was too widely viewed as a subsistence crop and food for the poor, when in reality it has enormous agro-industrial application and potential. One of these applications is processing into flour useful in baking and other food manufacturing purposes. The most immediate application of cassava flour is its partial substitution in bread and other baked products, but due to its different chemical properties, industrial-scale producers must make procedural adjustments. This catalogue draws an important distinction between fermented and unfermented cassava flours, and offers eight key technologies that promote the production and use of unfermented cassava flour and the better use of cassava by-products